Uranium frenzy : saga of the nuclear west - Ringholz, Raye Carleson (Utah State University Press, 2002)
Now expanded to include the story of nuclear testing and its consequences, Uranium Frenzy has become the classic account of the uranium rush that gripped the Colorado Plateau region in the 1950s. Instigated by the U.S. government's need for uranium to fuel its growing atomic weapons program, stimulated by Charlie Steen's lucrative Mi Vida strike in 1952, manned by rookie prospectors from all walks of life, and driven to a fever pitch by penny stock promotions, the boom created a colorful era in the Four Corners region and Salt Lake City (where the stock frenzy was centered) but ultimately went.